Machine Learning–Enhanced Threat Intelligence for Understanding the Underground Cybercrime Market - Naga Charan Nandigama (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The global expansion of digital networks has enabled cybercriminals to develop complex underground ecosystems that facilitate illegal trade, fraud, and coordinated cyber-attacks. Traditional security mechanisms struggle to accurately identify and profile illicit actors due to the high volume, velocity, and variety of cybercrime data generated across dark web forums, encrypted channels, and distributed threat infrastructures. This research proposes a unified analytics-powered framework integrating data engineering pipelines, data warehousing solutions, and advanced data science models to detect and profile threat actors within the cybercrime ecosystem. A scalable ETL/ELT architecture is designed for collecting and standardizing heterogeneous cyber intelligence sources, while a cloud-based warehouse supports high-performance analytical queries. Machine learning, graph analytics, and clustering methods are applied to uncover behavioral patterns, role hierarchies, and hidden relationships among cybercriminals. Experimental results demonstrate that the proposed system enhances actor identification accuracy, improves anomaly detection rates, and strengthens overall cyber-intelligence capabilities. The study concludes with recommendations for integrating automated pipelines into enterprise security operations. <!–StartFragment –>DOI: https://doi.org/10.17762/ijisae.v10i2s.7972<!–EndFragment –>